Pemanfaatan Keong Mas Untuk Pupuk Organik Cair di Kelompok Tani Podo Tentrem Kecamatan Wuluhan Jember - Suharjono Suharjono; Sepdian Luri Asmono; Rudi Wardana (Journal of Community Development, 2023)
The golden snail is one of the pests that damage rice plants, this pest has the ability to reproduce quickly, causing the golden snail to become one of the main pests in lowland rice. But the golden snail can be used as a basic material for liquid organic fertilizer (LOF) because it contains protein, Azotobacter, Azospirillum, phosphate solubilizing microbes, Pseudomonas, Staphylococcus, enzymes and the hormone auxin. The effectiveness of the golden snail LOF has been tested on several agricultural crops, one of which is rice. In the Podo Tentrem Farmers Group, these pests are simply thrown away and have not been utilized properly. Whereas the potential of this golden snail can be very high if it is processed into organic fertilizer. Therefore, with this community service activity, it is hoped that it can improve competence, skills and increase the production output of the Podo Tentrem farmer group. This can be measured by the enthusiasm of the participants who were attended by 100% of the invitees, besides that the participants also knew the stages of work and succeeded in making Keong Mas LOF well. In addition, other assessment indicators are using quantitative data on pre-test and post-test scores. Before the counseling was carried out, the pretest value was 50 and after the knowledge training, it increased with an average post-test score of 76. These results can indicate that in theory and practice, on average, participants understand and can make golden snail LOF.